BUSINESS COMPETITIVENESS STRATEGY OF PROCESSED MUSHROOM IN EAST JAVA: A RESOURCE-BASED VIEW MODEL APPROACH - Haryati, Novi; Choirunnisa, Yusti Mauriska (Jurnal Aplikasi Manajemen, 2020)
Mushrooms are one of the strategic agro-industrial commodities in Indonesia. It is because the mushroom market share for consumption is very high. People consume mushrooms as a snack, side dishes, and also as a main dish. The mushroom business in Malang Indonesia is very lively, especially in this city, there are many students and employees as consumers who like snacks on the sidelines of their activities. Due to many of those industries, the SME of mushroom needs to increase the production. Leading competitiveness in the product are the factors that must be kept by companies to be successful in their business. This research aims to understand the effect of tangible resources, entrepreneurship orientation, business uncertainty on competitive strategy, and the influence of competitive strategy on the company’s performance. The research uses methods such as quantitative descriptive analysis and inferential (SEM) based on Partial Least Square (PLS). Strategic resources, entrepreneurial orientation, and environmental uncertainty of mushroom small-medium enterprises have a direct effect more than an indirect effect. Strategic resources have the strongest significance if it is compared to entrepreneurial orientation and entrepreneurial uncertainty. Further research is needed to see the effect of competitive strategy on business performance.